2014
DOI: 10.1177/0954410014562483
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tip clearance size on the performance and tip leakage vortex in dual-rows counter-rotating compressor

Abstract: Based on the preliminary validation of the numerical results with an experiment, the steady results of different tip clearance size effects on the performance and tip leakage vortex of counter-rotating compressor were discussed. The predicted results showed that the stable margin and isentropic efficiency of the counter-rotating compressor decreased with increasing of the tip clearance size. Furthermore, increasing the tip clearance size had a greater negative effect on the performance of the upstream rotor th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 25 publications
2
30
0
Order By: Relevance
“…O4H topology was chosen to model the main flow passage, and butterfly topology was adopted to model the real tip clearance of rotors. Investigation of grid refinement was conducted by Wang et al 24 on the CRAC of current paper, and the results showed that the performance of the compressor keeps almost unchanged if the grid number exceeds to 2.5 Â 10 6 . Considering both accuracies and computational demands, grid number of 2.6 Â 10 6 approximately for the CRAC in the steady simulations and about 1.4 Â 10 6 for the two rotors in the unsteady numerical computations is adopted, respectively.…”
Section: Methodsmentioning
confidence: 95%
“…O4H topology was chosen to model the main flow passage, and butterfly topology was adopted to model the real tip clearance of rotors. Investigation of grid refinement was conducted by Wang et al 24 on the CRAC of current paper, and the results showed that the performance of the compressor keeps almost unchanged if the grid number exceeds to 2.5 Â 10 6 . Considering both accuracies and computational demands, grid number of 2.6 Â 10 6 approximately for the CRAC in the steady simulations and about 1.4 Â 10 6 for the two rotors in the unsteady numerical computations is adopted, respectively.…”
Section: Methodsmentioning
confidence: 95%
“…The validation work of the NUMECA FINE-Turbo has also been done by other researchers. Wang, Chen, Wu, and Ren (2014) have shown good agreements of compressor performance maps between the computed results and the experimental data in a counter-rotating axial compressor when using the Spalart-Allmaras model. Lange, Vogeler, Mailach, and Gomez (2013) have shown that the NUMECA FINE-Turbo-computed blade pressure distributions have quite good agreement with the experiment.…”
Section: Cfd Validationsmentioning
confidence: 68%
“…However, changes in these parameters are finally reflected with changes in integral parameters. Therefore, the verification method using integral parameters is widely applied in many researches [21,[24][25][26][27]. To verify the mesh independence, fans with mesh numbers of 3.82, 4.26, 4.65, 5.33 and 5.56 million are simulated in this study, as shown in Table 3.…”
Section: Meshingmentioning
confidence: 99%